Innovation indicators: a survey of innovative activities in the international food processed industry - Fornari, Vinicius C. B.; Gomes, Rogerio [UNESP]; Correa, Andre Luiz [UNESP] (Univ Estadual Campinas, Inst Geociencias, Dept Politica Cientifica & Tecn, 2015)
This paper seeks to combine traditional methods of measuring intensity with other alternative indicators to examine the dispersion of innovation activities in different industries and countries. The hypothesis that underlies the study lies in the fact that in the Food Processed Industry (IAP) the traditional methods are insufficient to detect the core of the innovation process. As method, we analyzed patent data extracted from the twenty-five largest food processed companies in the world and suggested different indicators developed from the Pesquisa de Inovacao Tecnologica (PINTEC, 2010) - for Brazilian companies - and the Community Innovation Survey (CIS, 2009) - for European Union companies. The results allowed us to establish relationships in three dimensions: (i) the complexity of the innovative effort of the IAP; (ii) the efforts to innovation in different countries are distinct and; (iii) there is heterogeneity in country performance.
Keywords: Technological Diffusion; Innovative Activity; Food Processed Industry